Mechanical And Biological Performance Of Sodium Metaperiodate-Impregnated Plasticized Wood (Pw) - Md. Rezaur, Rahman; Sinin, Hamdan; Abu Saleh, Ahmed; Md. Saiful, Islam (BioResources, 2010)
Malaysia, especially the Borneo Island state of Sarawak, has a large variety of tropical wood species. In this study, selected raw tropical wood species namely Artocarpus Elasticus, Artocarpus Rigidus, Xylopia spp., Koompassia Malaccensis, and Eugenia spp. were chemically treated with sodium metaperiodate to convert them into plasticized wood (PW). Manufactured plasticized wood samples were characterized using, Fourier transform infrared spectroscopy, scanning electron microscopy, and mechanical testing (modulus of elasticity (MOE), modulus of rupture (MOR), static Young’s modulus (Es), decay resistance, and water absorption). MOE and MOR were calculated using a three-point bending test. Es and decay resistance were calculated using the compression parallel to grain test and the natural laboratory decay test, respectively. The manufactured PW yielded higher MOE, MOR, and Es. PW had a lower water content compared to the untreated wood and had high resistance to decay exposure, with Eugenia spp. having the highest resistance compared to the others.